Role of Career Counselling in Medical Profession: Perceptions of Medical Students - Hina Ahmed; Abdullah Yousaf; Muhammad Ahmed; Muhammad Tauqeer Akhtar (University of Lahore, 2024)
Objective: To determine the perception of medical students regarding the role of career counselling in medical profession. Methodology: It was a cross sectional study done between April and October 2023, where140 medical students from Central Park Medical College, Lahore were enrolled via convenience sampling. After receiving formal IRB approval, data was collected via self-designed google forms and WhatsApp groups from MBBS students in their first to final academic year who volunteered to participate after piloting with Cronbach Alpha score of 0.81. After collecting data, SPSS software version 26 was utilized for analysis. The outcomes were presented as frequency tables and bar graphs. Results: A total of 140 responses were collected with the average age of the respondents being 21+1.7SD years. About 59 (42.1%) of the students who responded were from 2nd year MBBS, 38 (27.1%) were from 4th year MBBS, 26 (19%) were from 1st year MBBS, 09 (6%) were from 5th year MBBS and remaining 08 (6%) were from 3rd year MBBS. About 60 (42.9%),52 (37.1%), 133 (95%) and 131 (93.6%)of the students said that career counselling helped identify their capabilities. About 130 (93 %), 115 (82 %), and 113(81%) gave positive responses when asked about the impact on gaining perspective, developing strategies, and managing conflicts. There was a significant relationship between the role of career counselling in identifying opportunities and building the CV 109(95%) (p=0.01), understanding interest59(99%) capabilities49(94%) (p=0.00), broadening one's perspective 126(95%) (0.00), adopting the right strategies 126(97%) (0.00), and resolving conflicts 108(95%) (0.00). Conclusion: Career counselling should be conducted in the early years of medical professional's career, so that students can identify their areas of interest in order to choose the appropriate specialization in the future.